On a Model of Generalized Pell Numbers - Craveiro, I. M.; Spreafico, E. V. Pereira; Rachidi, M. (International Journal of Advanced Engineering Research and Science, 2021)
In this study we investigate a model of generalized Pell numbers. Combinatorial representations are provided and some new identities and combinatorial identities are established. Moreover, analytic results are exhibited, where some special cases are discussed. Illustrative examples and applications are given.